## Solving the Equation: 0.5(x - 3) = 0.6(4 + x) - 2.6

This article will guide you through the steps of solving the equation **0.5(x - 3) = 0.6(4 + x) - 2.6**.

### Step 1: Distribute

Begin by distributing the constants on both sides of the equation:

**Left side:**0.5 * x - 0.5 * 3 = 0.5x - 1.5**Right side:**0.6 * 4 + 0.6 * x - 2.6 = 2.4 + 0.6x - 2.6

The equation now becomes: **0.5x - 1.5 = 2.4 + 0.6x - 2.6**

### Step 2: Combine Like Terms

Simplify both sides by combining the constant terms:

**Right side:**2.4 - 2.6 = -0.2

The equation now becomes: **0.5x - 1.5 = 0.6x - 0.2**

### Step 3: Isolate x

To isolate the variable *x*, subtract **0.5x** from both sides of the equation:

**0.5x - 0.5x - 1.5 = 0.6x - 0.5x - 0.2**

This simplifies to: **-1.5 = 0.1x - 0.2**

### Step 4: Solve for x

Add **0.2** to both sides of the equation:

**-1.5 + 0.2 = 0.1x - 0.2 + 0.2**

This simplifies to: **-1.3 = 0.1x**

Finally, divide both sides by **0.1** to get the value of *x*:

**-1.3 / 0.1 = 0.1x / 0.1**

Therefore, **x = -13**.

### Conclusion

By following these steps, we have successfully solved the equation **0.5(x - 3) = 0.6(4 + x) - 2.6** and found that **x = -13**.